Genotype Driven Therapy for Non-Small Cell Lung Cancer: Resistance, Pan Inhibitors and Immunotherapy - Singh, Sitanshu S.; Dahal, Achyut; Shrestha, Leeza; Jois, Seetharama D. (Current Medicinal Chemistry, 2020)
Eighty-five percent of patients with lung cancer present with Non-small Cell Lung Cancer (NSCLC). Targeted therapy approaches are promising treatments for lung cancer. However, despite the development of targeted therapies using Tyrosine Kinase Inhibitors (TKI) as well as monoclonal antibodies, the five-year relative survival rate for lung cancer patients is still only 18%, and patients inevitably become resistant to therapy. Mutations in Kirsten Ras Sarcoma viral homolog (KRAS) and epidermal growth factor receptor (EGFR) are the two most common genetic events in lung adenocarcinoma; they account for 25% and 20% of cases, respectively. Anaplastic Lymphoma Kinase (ALK) is a transmembrane receptor tyrosine kinase, and ALK rearrangements are responsible for 3-7% of NSCLC, predominantly of the adenocarcinoma subtype, and occur in a mutually exclusive manner with KRAS and EGFR mutations. Among drug-resistant NSCLC patients, nearly half exhibit the T790M mutation in exon 20 of EGFR. This review focuses on some basic aspects of molecules involved in NSCLC, the development of resistance to treatments in NSCLC, and advances in lung cancer therapy in the past ten years. Some recent developments such as PD-1-PD-L1 checkpoint-based immunotherapy for NSCLC are also covered.
Keywords: Tyrosine Kinase Inhibitors (TKIs)